Beam‐Induced Fe Nanopillars as Tunable Domain‐Wall Pinning Sites. (12th February 2014) - Franken, Jeroen H.; van der Heijden, Mark A. J.; Ellis, Tim H.; Lavrijsen, Reinoud; Daniels, Carsten; McGrouther, Damien; Swagten, Henk J. M.; Koopmans, Bert
<x xml:space="preserve">Abstract</x> Focused‐electron‐beam‐induced deposition (FEBID) is employed to create freestanding magnetic nanostructures. By growing Fe nanopillars on top of a perpendicular magnetic domain wall (DW) conduit, pinning of the DWs is observed due to the stray fields emanating from the nanopillar. Furthermore, a different DW pinning behavior is observed between the up and down magnetic states of the pillar, allowing to deduce the switching fields of the pillar in a novel way. The implications of these results are two‐fold: not only can 3‐dimensional nano‐objects be used to control DW motion in applications, it is also proposed that DW motion is a unique tool to probe the magnetic properties of nano‐objects.